2020
DOI: 10.3390/ijerph17238885
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Polish Seniors toward the Use of Public Space during the First Wave of the COVID-19 Pandemic

Abstract: The number of seniors rises worldwide. The lockdown of public institutions caused by COVID-19 influenced the lives of many of them. In the new reality, owners and managers of public spaces need to rethink the way they provide their services, and redesign public spaces to meet the needs of senior citizens. This requires the recognition of the needs of seniors concerning the use of public spaces in the times of the COVID-19 hazard. To investigate this issue, survey studies with 1000 respondents aged 65+ were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…The oldest seniors (aged over 80) declared that limitations concerning the possibility of going shopping independently created a psychological load resulting from the isolation. Among other problems, the seniors also indicated longing for an additional occupational activity, contact with physicians, and the possibility to travel [35]. The above-mentioned data were also confirmed by a previously mentioned study in which nearly a half of respondents (46%) reported that during the time of the pandemic they reduced their social contacts, which consequently decreased their quality of life.…”
Section: Multi-annual Programme 'Senior+supporting
confidence: 69%
See 2 more Smart Citations
“…The oldest seniors (aged over 80) declared that limitations concerning the possibility of going shopping independently created a psychological load resulting from the isolation. Among other problems, the seniors also indicated longing for an additional occupational activity, contact with physicians, and the possibility to travel [35]. The above-mentioned data were also confirmed by a previously mentioned study in which nearly a half of respondents (46%) reported that during the time of the pandemic they reduced their social contacts, which consequently decreased their quality of life.…”
Section: Multi-annual Programme 'Senior+supporting
confidence: 69%
“…It is noteworthy that the lack of physical activity in combination with hindered access to the health sector may have significantly contributed to the increase in mortality in this age group. A study conducted between April-May 2020 concerning the needs and concerns accompanying the elderly in the light of changes in social life caused by the presence of coronavirus COVID-19, confirmed an intensification of the feeling of fear while using public space (55% of seniors declared such concerns) [35]. The feeling of fear while using public space was significantly related with the limitation of social contacts.…”
Section: Multi-annual Programme 'Senior+mentioning
confidence: 93%
See 1 more Smart Citation
“…Equations (1) and (2) describe the governing equations of the fluid phase [12]. The buoyancy effect of air is modeled with the Boussinesq approximation.…”
Section: Methodologiesmentioning
confidence: 99%
“…The results in the survey study of Fabisiak et al [2] indicated that 55% of respondents will be afraid to use public spaces after the COVID-19 lockdown. Restrictions on the use of public spaces and physical distancing have been key policy measures to reduce the transmission of COVID-19 and protect public health [3].…”
Section: Introductionmentioning
confidence: 99%